Aₙᵇ = a!/(a - b)!
a>b a b натуральные
a! = 1*2*3*....*(a-1)*a
==================
Aₓ³ = 1/20 * Aₓ⁴
x>=4
x!/(x - 3)! = 1/20*x!/(x-4)!
x(x-1)(x-2) = 1/20*x(x-1)(x-2)(x-3)
20x(х - 1)(х - 2) = x(x - 1)(x - 2)(x - 3)
20x(х - 1)(х - 2) - x(x - 1)(x - 2)(x - 3) = 0
x(х - 1)(х - 2)[20 - (x - 3)] = 0
x(х - 1)(х - 2)(23 - x) = 0
x1=0 x>3 НЕТ
x2=1 x>3 Нет
x3=3 x>3 Нет
x4 = 23
Ответ x=23
20(х - 1)(х - 2) = (x - 1)(x - 2)(x - 3);
20(х - 1)(х - 2) - (x - 1)(x - 2)(x - 3) = 0;
(х - 1)(х - 2)(20 - (x - 3)) = 0;
(х - 1)(х - 2)(20 - x + 3) = 0;
(х - 1)(х - 2)(23 - x) = 0;
x₁ = 1; x₂ = 2 - не удовлетворяют уравнение; x₃ = 23.
Ответ: 23.
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Aₙᵇ = a!/(a - b)!
a>b a b натуральные
a! = 1*2*3*....*(a-1)*a
==================
Aₓ³ = 1/20 * Aₓ⁴
x>=4
x!/(x - 3)! = 1/20*x!/(x-4)!
x(x-1)(x-2) = 1/20*x(x-1)(x-2)(x-3)
20x(х - 1)(х - 2) = x(x - 1)(x - 2)(x - 3)
20x(х - 1)(х - 2) - x(x - 1)(x - 2)(x - 3) = 0
x(х - 1)(х - 2)[20 - (x - 3)] = 0
x(х - 1)(х - 2)(23 - x) = 0
x1=0 x>3 НЕТ
x2=1 x>3 Нет
x3=3 x>3 Нет
x4 = 23
Ответ x=23
Verified answer
20(х - 1)(х - 2) = (x - 1)(x - 2)(x - 3);
20(х - 1)(х - 2) - (x - 1)(x - 2)(x - 3) = 0;
(х - 1)(х - 2)(20 - (x - 3)) = 0;
(х - 1)(х - 2)(20 - x + 3) = 0;
(х - 1)(х - 2)(23 - x) = 0;
x₁ = 1; x₂ = 2 - не удовлетворяют уравнение; x₃ = 23.
Ответ: 23.